Blue light hours : a novel - Dantas Lobato, Bruna (Black Cat, 2024)
"From the National Book Award-winning translator, an atmospheric and wise debut novel of a young Brazilian woman's first year in America, a continent away from her lonely mother, and the relationship they build over Skype calls across borders. In a small dorm room at a liberal arts college in Vermont, a young woman settles into the warm blue light of her desk lamp before calling the mother she left behind in northeastern Brazil. Four thousand miles apart and bound by the angular confines of a Skype window, they ask each other a simple question: What's the news? Offscreen, little about their lives seems newsworthy. The daughter writes her papers in the library at midnight, eats in the dining hall with the other international students, and raises her hand in class to speak in a language the mother cannot understand. The mother meanwhile preoccupies herself with natural disasters, her increasingly poor health, and the heartbreaking possibility that her daughter might not return to the apartment where they have always lived together. Yet in the blue glow of their computers, the two women develop new rituals of intimacy and caretaking, from drinking whiskey together in the middle of the night to keeping watch as one slides into sleep. As the warm colors of New England autumn fade into an endless winter snow, each realizes that the promise of spring might mean difficult endings rather than hopeful beginnings. Expanded from a story originally published in The New Yorker, Bruna Dantas Lobato paints a powerful portrait of a mother and a daughter coming of age together and apart and explores the profound sacrifices and freedoms that come with leaving a home to make a new one somewhere else"--